PRODUCING CERAMIC OXIDE (Y 0.8 to 0, 2) Ba2Cu3O7 BY SOL-GEL METHOD - M. Osorio, Ana (2005)
On the base of the ceramic superconductor YBa2Cu307 obtained by SOL-GEL process whose critic temperature reached was 92 K. A new doped structure has been synthesized with calcium, in which the Ytrio has been replaced by the calcium in stoichiometry proportion Y:Ca = 0,8: 0,2 . The precursors obtained with the help of oxalate stoichiometry have been modified with calcium nitrate. The obtained matrize was treated thermally 860 ºC and 880 ºC. The characterization has been carrie through the technique of X Rays Diffraction obtained showed that the obtained materials present a high crystalline grade and a good correspondence in their crystalline structures corresponding to each superconductivity phase.